Effectiveness of structural funds - microlevel perspective (case of Slovakia) - Miroslav Šipikal (European Regional Science Association (ERSA), 2011)
Cohesion policy and regional policy as a main part of cohesion policy are the most important policies of European Union. This could also be view from the volume of financial resources allocated for these policies. One of the main current research issues is analyzing efficiency and effectiveness of these funds. Examining the effectiveness of funds we can see a number of shortcomings, from which are the most significant deadweight loss effects, subtitution effect, lack of application of the principles of partnership, administrative burden focused on expenses and not results or the low multiplier effects. We have analyzed several of them directly in the case study of some Slovak regions.
Keywords: 330